G76(P) The Incidence and natural history of Paediatric Inflammatory Bowel Disease Unclassified in Scotland. (7th April 2014) - Cameron, FL; Henderson, P; Wilson, DC
Abstract : Background: Inflammatory Bowel Disease Unclassified (IBDU) accounts for ~10% of paediatric IBD (PIBD). The natural history of IBDU includes potential evolution to Crohn's disease (CD) or ulcerative colitis (UC). We aimed to describe the incidence and the natural history of paediatric IBDU in a population-based cohort. Methods: Incidence of IBDU was collected over a 10-year period (01/03–12/12) from the two largest Scottish paediatric gastroenterology networks (serving 74.4% of Scottish population <16 years). Demographics, diagnostic investigation and follow-up data were obtained until study end (31.10.13; unless prior transition or emigration) to ascertain reclassification of IBD subtype, clinical progress and outcome at last follow up. Incidence rates and trends were calculated using publicly available population data and statistics generated using Poisson regression. Results: 65 patients were IBDU (57% male) at diagnosis with a median age of 11.3yrs (range 2.6–15.9). The age adjusted incidence of IBDU was 0.65/100, 000/yr (95% CI 0.42–0.97) in the 5-year epoch 2003–2007 and 1.14/100, 000/yr (95% CI 0.81–1.56) for 2008–2012, a non-significant increase (p = 0.068). All patients had colonoscopy (74% ileal intubation), 62 (95%) had an upper GI endoscopy; remaining 3 had small bowel imaging. 61 (94%) had radiological imaging, 44 (68%) had a barium meal and follow through with 15 (23%) having MR enterography. At diagnosis, 53 (82%) had a pancolitis, 4 (6%) had disease distal to the hepatic flexure, 5 (8%) had disease distal to the splenic flexure and 3 (4%) had proctitis. 37 (57%) had mild disease (defined as mild infrequent relapses) while 7 (11%) had severe chronically active disease. Median follow-up was 3.1yrs (range 0.4–6.8). 16 (25%) had their diagnosis changed (all after endoscopic re-evaluation) after a median of 1.6yrs (range 0.6–5.7), to CD in 11 and UC in 5; 10 (15%) remained IBDU. Conclusions: Incidence of IBDU showed a non-significant trend to rise during the 10 year study period. 25% had their diagnosis changed after endoscopic re-evaluation, more than previously reported by systematic review (Prenzel and Uhlig 2009) after median follow up of 1.6years. Most cases had inactive/mild disease activity; a minority remained IBDU despite re-assessment.